Uporaba univerzalne haptične naprave v rehabilitaciji roke in zapestja pri bolniku po hudi nezgodni možganski poškodbi - Kuret, Zala (Rehabilitacija (Ljubljana), 2010)
Aim: Patient rehabilitation after upper motor neuron lesion with upper limb motor deficits requires repeating movements and individual therapeutic treatment. In order to achieve better focus and motivation during training, we performed a rehabilitation program for hand and wrist with a patient after traumatic brain injury by using universal haptic device. The paper presents the effects of the treatment. Methods: 16-year old left-handed high-school student was included in outpatient rehabilitation treatment one year after traumatic brain injury. At first examination, there were signs of left-sided spastic hemiparesis with increased muscle tone in flexors of wrist and fingers, and in pronators, there was limited range of movement in the direction of wrist extension and forearm supination. Finger grip was weak, stiloradial and stiloulnar tendon reflexes were exaggerated. Sensitivity on upper limb was preserved. Within the occupational therapy program, we performed Jebsen function hand test. The patient completed 10 training session for wrist flexion and extension and for pro- and supination of forearm using universal haptic device. In rehabilitation of hand or wrist, the design of the universal haptic device enables exercises in two different modes, "hand" or "wrist", with two degrees of movement freedom. Results: The case supports the hypothesis that patients after traumatic brain injury can improve motor skills and mobility of paretic upper limb, but with the exception of limb function. This is supported by the fact that the patient required increasingly lesser degree of support by haptic device for performance of movement in the same range and the same precision in each session, but there were just slight changes in hand function. Conclusion: The described case indicates the possibility that the method can be and effective complementary type of treatment in complex rehabilitation of patients with upper motor neuron lesion.
Keywords: motorične motnje; možganske poškodbe; rehabilitacija; robotika; vocational rehabilitation